Zaokroženi nosni samoglasniki v Brižinskih spomenikih - Kortlandt, Frederik (Slavistična revija, 1996)
Georg Holzer opposes my argumentation, expressed twenty years ago, that the reflexes of jers and nasal vowels in the Freising Fragments reflect the Proto-Slavic accentual system existing before the operation of the progressive accent shift, which is characteristic of all Slovenian dialects. In a recent article, Robert Woodhouse has proposed to modify Holzer's rule by means of five additional ad hoc assumptions. - These two articles have not given me reason to change my opinion about this problem.
Keywords: Brižinski spomeniki; Freising manuscripts; glasoslovje; nosniki; Phonetic sciences; samoglasniki; Slovene; slovenščina